Outgroup evaluation and social identity among boys and girls as related to parental occupation and residence (Journal of Life and Earth Science, 2011)
The study attempted to investigate social identity and out-group evaluation in adolescent boys and girls in relation to parental occupation and residential background. The study used a sample composed of 320 respondents. An Adjective Check List was used for data collection. A three way analysis of variance involving 2 levels of gender (boys/girls), 2 levels of parental occupation (business/service) and 2 levels of residence (urban/rural) was used for the computation of results. Results showed gender, parental occupation and residence had statistically significant effects on the respondents. A two-way interaction between profession and residence was also statistically significant. Respondents with service background evaluated out-group significantly less positively as compared to the respondents with business background. Again, girls evaluated out-group significantly less positively as compared to the boys. Moreover, respondents with urban residence evaluated out-group significantly less positively as compared to the respondents with rural residence. Key words: Social identity; self-depreciation; parental occupation; misidentified perception; racial identification. DOI: 10.3329/jles.v5i0.7351 J. Life Earth Sci., Vol. 5: 57-61, 2010